2011
DOI: 10.1017/s0144686x11000614
|View full text |Cite
|
Sign up to set email alerts
|

To feel safe in everyday life at home – a study of older adults after home modifications

Abstract: The aim of this study was to explore aspects contributing to experiences of safety in everyday life for older adults who have received modification services. Qualitative interviews were conducted with eight people. Data were analysed using a comparative approach. Three main categories emanated in the analysis: prerequisites that enable a feeling of safety, strategies that enable safety in everyday life, and use of and reliance on technology impacts on safety. The findings revealed that to feel safe in everyday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
4
36
1
Order By: Relevance
“…The findings show that the cohabitants' hopes and expectations of the HA above all concern the partner's mobility, safety and independence in activities of everyday life in and around the home. This is in line with the aims of the intervention to promote safe and independent living for people with disabilities in ordinary housing (8) and in line with previous research on how HAs are evaluated and perceived by the applicant (17,19,30).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings show that the cohabitants' hopes and expectations of the HA above all concern the partner's mobility, safety and independence in activities of everyday life in and around the home. This is in line with the aims of the intervention to promote safe and independent living for people with disabilities in ordinary housing (8) and in line with previous research on how HAs are evaluated and perceived by the applicant (17,19,30).…”
Section: Discussionsupporting
confidence: 85%
“…This is in line with the aims of the intervention to promote safe and independent living for people with disabilities in ordinary housing [8], and in line with previous research on how HAs are evaluated and perceived by the applicant [17,19,31,32].…”
Section: Housing Decisionssupporting
confidence: 81%
See 1 more Smart Citation
“…Safety is a basic need related to subjective well‐being . Feeling safe is important to older people and Scandinavian qualitative studies have found that PHV may improve feeling of safety among users . We found that the majority of the respondents did not need help from PHV related to feelings of safety, but that the importance of PHVs regarding older people's feelings of safety increases with age, which was not reported previously.…”
Section: Discussioncontrasting
confidence: 53%
“…The barriers due to impairments of elders' physical status are cognitive (memory and processing speed, visual, auditory, and motor control abilities [23]). The mental barriers are attitudinal (manner of feeling or behaving; [24,25]) privacy concerns, security [26], safety (monitoring elderly in their private home; [27][28][29][30][31]), and total replacement of humans with technology tools such as robots [32,33]. Also, much of the literature on human factors in HRI has emphasized the importance of perceived safety, usefulness, self-efficacy, learning support, and experience, etc.…”
Section: Human Factorsmentioning
confidence: 99%